Technology intensification and farmers’ welfare: A case study from Karnataka, a semi-arid state of India - Kapoor, Shreya; Pal, Barun Deb; Singhal, Aditi; Anantha, K.H. (SAGE Publications, 2025)
JEL Codes: Q16, Q54, Q55, C13